ANALISIS KESULITAN MEMBACA TEKS BAHASA INGGRIS PADA SISWA KELAS V SDN CIPELANG GEDE (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study on the analysis of difficulties in reading English texts is based on a case study of students who experienced difficulties in reading English texts in grade V at SDN Cipelang Gede in the 2024/2025 academic year. The objectives of this study are to identify the factors that influence students' difficulties in reading English texts and to develop and recommend effective learning strategies to overcome these difficulties among fifth-grade students. This research was conducted at SDN Cipelang Gede from April to August 2025. This research used a descriptive quantitative method with a population of 34 students, and sampling was done using purposive sampling. The data collection techniques used were questionnaires, interviews, and documentation. The results of the study show that students experience difficulties in reading English texts (79.41%), understanding the content of English texts (85.29%), and retelling the content of English texts (67.65%). There are internal and external factors that cause students to have difficulty reading English texts. The internal factors experienced by students are boredom during learning (76.47%), difficulty in pronunciation (70.59%), difficulty in memorizing vocabulary (55.88%), and difficulty in understanding grammar rules (52.94%). In addition, there are external factors that affect students, namely the use of learning media (47.0%) and low levels of student learning at home (35.29%).